(untitled) (Homoeopathy for All, 2023)
Hypothyroidism (Also Known As Underactive Thyroid) Is A State In Which The Thyroid Gland Does Not Make Enough Thyroid Hormone. Since The Main Purpose Of Thyroid Hormone Is To “Run The Body’s Metabolism”, It Is Understandable That People With This Condition Will Have Symptoms Associated With A Slow Metabolism. This Article Provides An Overview of The Aetiology, Diagnosis, And Appropriate General & Homoeopathic Management of Underactive Thyroid.